Propuesta para el desarrollo del agroturismo en el sector Rosa Amelia del cantón Buena Fe, provincia de Los Ríos, año 2022 - Cerezo Campos, Rider Jarley (2022)
The present investigation was carried out in the Rosa Amelia sector, Buena Fe canton, Los Ríos province. The objective of this work was to develop a proposal for agrotourism development for the benefit of the Rosa Amelia sector of the Buena Fe canton and thus strengthen the economic and productive activity of the community, motivating farm owners